PERAN ORANG TUA ANAK BERKEBUTUHAN KHUSUS (AUTIS) SEKOLAH DASAR SELAMA MASA COVID-19 - Ika Firma Ningsih Dian Primasari; Asep Supena (Universitas Negeri Medan, 2020)
Abstract: This study aims to describe the role of parents in accompanying children with special needs (autism) in primary schools during the Covid-19 pandemic. This study uses a qualitative research method with a descriptive case study approach, which describes specific, limited, in-depth cases using various sources, such as interviews, observations, documents, in order to obtain an in-depth understanding and analysis of the case (Creswell, 2015). Data collection methods, namely: interviews, observation, monitoring notes. Interviews, with 6 informants, consisting of main informants, namely 4 parents and supporting informants, namely 1 teacher at the SD Lazuardi Inclusive School and 1 therapist at one of the ABA therapy clinics. Informants in this study were selected based on the characteristics of parents who have autistic children at the age of 7-14 years, namely elementary school age children. There were 6 informants consisting of the main informants, namely 4 parents and supporting informants, namely 1 teacher at the Lazuardi Elementary School and 1 therapist at one of the ABA therapy clinics. The validity of the data in this study used triangulation in the data collection method, through interviews with main informants, namely parents, as well as supporting informants, namely child therapists in clinics who came home to home visits and teachers at school. Data analysis techniques use thematic analysis, namely first, preparing and organizing data (text data such as transcripts, or image data such as photos), then reducing the data to themes through the coding process and summarizing the code, and finally presenting the data in the form of charts, tables, or discussion (Creswell, 2015). The results of this study get an overview of the role of parents, namely maintaining and ensuring children to implement a clean and healthy life, accompanying children to study at home online and by home visit (teachers come home) during the Covid-19 pandemic period according to the teacher's health protocol and students must wear masks. and maintaining distance, accompanying children with therapy at home home visits (therapists come to the house), accompanying children on activities (playing, learning, teaching worship), monitoring child development, managing diet, and financing therapy and school funding. The role of parents is very important, the existence of autistic children makes parents more receptive, sincere and patient, understanding and able to find solutions. Routines are important activities for children with autism. Keywords: role of parents, autistic children, covid-19. Abstrak: Penelitian ini bertujuan untuk menggambarkan peran orangtua dalam mendampingi anak berkebutuhan kusus (autis) sekolah dasar selama masa pandemic covid-19. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus deskriptif, yaitu mendeskripsikan kasus yang spesifik, terbatas, mendalam dengan menggunakan beragam sumber, seperti wawancara, pengamatan, dokumen, supaya diperoleh pemahaman dan analisa secara mendalam tentang kasus tersebut (Creswell, 2015). Metode pengumpulan data yaitu: wawancara, observasi, catatan monitoring. Wawancara, dengan 6 informan, yang terdiri dari informan utama yaitu 4 orangtua dan informan pendukung yaitu 1 orang guru di Sekolah Inklusi SD Lazuardi dan 1 orang terapis di salah satu klinik terapi ABA. Informan dalam penelitian ini dipilih berdasarkan karakteristik orangtua yang mempunyai anak autis pada usia 7-14 tahun yaitu anak usia sekolah dasar. Informan sebanyak 6 orang terdiri dari informan utama yaitu 4 orangtua dan informan pendukung yaitu 1 orang guru di Sekolah Dasar Lazuardi dan 1 orang terapis di salah satu klinik terapi ABA. Keabsahan data dalam penelitian ini menggunakan Triangulasi pada metode pengumpulan data, melalui wawancara dengan informan utama, yaitu orang tua, serta informan pendukung, yaitu terapis anak di klinik yang datang rumah home visit serta guru di sekolah. Teknik analisa data menggunakan analisa tematik yaitu pertama, menyiapkan dan mengorganisasikan data (data teks seperti transkrip, atau data gambar seperti foto), kemudian mereduksi data tersebut menjadi tema melalui proses pengodean dan peringkasan kode, dan terakhir menyajikan data dalam bentuk bagan, tabel, atau pembahasan (Creswell, 2015). Hasil dari penelitian ini mendapatkan gambaran peran orangtua yaitu menjaga dan memastikan anak untuk menerapkan hidup bersih dan sehat, mendampingi anak belajar dirumah secara online maupun secara home visit (guru datang kerumah) selama masa pandemic covid-19 sesuai protocol kesehatan guru dan murid wajib menggunakan masker dan menjaga jarak, mendampingi anak terapi dirumah home visit (terapis datang kerumah), menemani anak beraktivitas (bermain, belajar, mengajarkan ibadah), pemantauan perkembangan anak, pengelolaan diet, serta pembiayaan terapi dan pembiayaan sekolah. Peran orang tua sangat penting, keberadaan anak autis menjadikan orangtua lebih mampu menerima, ikhlas dan sabar, memahami dan mampu mencari solusi. Rutinitas merupakan aktivitas penting bagi anak autis. Kata Kunci: peran orangtua, anak autis, covid-19.